Electric power generation through dairy waste in microbial fuel cells (LACCEI, 2024)
Abstract– The increase in the human population has generated that the consumption of different types of dairy products also increases, because it is one of the main foods in the diet in the early life of each human being. This has caused the waste of this type of food to increase in the same way, which is why a way to use it eco-friendly has been sought, found in microbial fuel cells a way to generate electricity in a sustainable manner. In this research, milk waste was used as fuel in microbial fuel cells on a laboratory scale, managing to generate electrical current and voltage peaks of 4.125 ± 0.347 mA and 1.104 ± 0.101 V with an optimum operating pH of 7.46 ± 0.35 whose electrical conductivity of the substrate was 119.373 ± 4.59 mS/cm, all this on day 21. Likewise, the maximum power density was calculated at 443.765 ± 26.738 mW/cm2 with a current density of 5.257 A/cm2 and showing a voltage of 1005.78 ± 13.54 mV, all this operating with an internal resistance of 61.795 ± 8.691 Ω. Finally, the three microbial fuel cells were connected in series, managing to generate 2.66 V, enough to light a red LED light. In this way, an innovative way of generating electricity on a small scale is given, giving great hope to livestock companies to reuse their waste in a beneficial way for themselves.